2017
DOI: 10.1038/ncomms15872
|View full text |Cite
|
Sign up to set email alerts
|

Current rates and mechanisms of subsea permafrost degradation in the East Siberian Arctic Shelf

Abstract: The rates of subsea permafrost degradation and occurrence of gas-migration pathways are key factors controlling the East Siberian Arctic Shelf (ESAS) methane (CH4) emissions, yet these factors still require assessment. It is thought that after inundation, permafrost-degradation rates would decrease over time and submerged thaw-lake taliks would freeze; therefore, no CH4 release would occur for millennia. Here we present results of the first comprehensive scientific re-drilling to show that subsea permafrost in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 46 publications
5
132
0
2
Order By: Relevance
“…Subsea permafrost degradation rates derived from the CryoGRID2 model results with salt diffusion for the Bykovsky Peninsula (scenario A), and the geoelectric results are compared to published subsea permafrost degradation rates in Siberia. The studies include long‐term (i.e., since inundation) and recent degradation rates from borehole work at Muostakh Island (Shakhova et al, ; Kunitsky, ), as well as degradation rates derived from a borehole at the Buor‐Khaya Peninsula (Overduin et al, ), several boreholes in the Western Laptev Sea (Overduin et al, ), and geoelectric results offshore of Muostakh Island (Overduin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsea permafrost degradation rates derived from the CryoGRID2 model results with salt diffusion for the Bykovsky Peninsula (scenario A), and the geoelectric results are compared to published subsea permafrost degradation rates in Siberia. The studies include long‐term (i.e., since inundation) and recent degradation rates from borehole work at Muostakh Island (Shakhova et al, ; Kunitsky, ), as well as degradation rates derived from a borehole at the Buor‐Khaya Peninsula (Overduin et al, ), several boreholes in the Western Laptev Sea (Overduin et al, ), and geoelectric results offshore of Muostakh Island (Overduin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of subsea permafrost on the Laptev Sea shelf can be hundreds of meters thick (Romanovskii et al, ), and its presence may extend up to 350 km offshore (Soloviev, ). Offshore of Muostakh Island, repeated borehole measurements separated by 31–32 years indicated an ice‐bearing subsea permafrost degradation rate of 0.14 m/year (Shakhova et al, ). Furthermore, geoelectric observations offshore of Muostakh Island showed that the degradation rate of ice‐bearing subsea permafrost decreased from 0.4 m/year immediately after inundation to 0.1 m/year 60–110 years after submergence from coastal erosion (Overduin et al, ).…”
Section: Study Areamentioning
confidence: 99%
“…Remobilization of old permafrost carbon to Chukchi Sea sediments during the end of the last deglaciation. The current shallow sea north of Siberia was then above sea level, exposed to the atmosphere and hosted permafrost-dominated tundra landscapes (Hubberten et al, 2004;Romanovskii et al, 2000;Shakhova et al, 2017). The current shallow sea north of Siberia was then above sea level, exposed to the atmosphere and hosted permafrost-dominated tundra landscapes (Hubberten et al, 2004;Romanovskii et al, 2000;Shakhova et al, 2017).…”
Section: Citationmentioning
confidence: 99%
“…Thus, water heating leads to additional increasing pCO 2 in the surface water. We also suggest that progression of sub-sea permafrost thawing and decrease in ice extent could result in a significant increase in carbon discharge from the sea floor (Nicolsky and Shakhova, 2010;Shakhova et al, 2014Shakhova et al, , 2015Shakhova et al, , 2017Vonk et al, 2014) producing additional CO 2 .…”
Section: The Laptev Seamentioning
confidence: 99%